Boosting Student Engagement in English Writing through the Small Moments Strategy - Sulfaedah Lestary (Hasanuddin University, 2025)
This research aims to explore how the Small Moments strategy can increase student involvement in the English language learning process, especially in writing skills. The research method used is a case study in a junior high school (SMP), where students are grouped into several groups and then each group applies the Small Moments strategy. Data was collected through observation, interviews, and analysis of students' writing before and after the intervention. The results showed that students who engaged in the Small Moments strategy showed significant increases in their motivation, creativity and writing abilities. Students are more active in sharing personal experiences and relating these experiences to the writing context, which in turn increases their sense of ownership of the work produced. These findings indicate that implementing the Small Moments strategy is not only effective in improving writing skills, but can also create a more inclusive and interesting learning environment. This research recommends implementing similar strategies in teaching English and other subjects to increase student engagement.